The impact of yoga on stress, metabolic parameters, and cognition of Indian adolescents: A cluster randomized controlled trial - Harish Ranjani; Narayanaswamy Jagannathan; Tina Rawal; Radhakrishnan Vinothkumar; Nikhil Tandon; Jayaram Vidyulatha; Viswanathan Mohan; Yashdeep Gupta; Ranjit Mohan Anjana (Integrative Medicine Research, 2023)
Background: This project aimed to assess the impact of yoga on stress, metabolic parameters and cognition (attention & concentration) in adolescents, aged 13–15 years from public and private schools in two cities (Chennai and New Delhi) in India. Methods: The study recruited 2000 adolescents from 24 schools in a cluster randomized controlled trial design. The yoga group participants underwent 17 yoga sessions, which included: pranayama, basic asanas, meditation and relaxation exercises. Yoga sessions, were held in the school premises once a week. A total of five awareness talks on healthy lifestyle were delivered once a month to the education group. ADOlescence Stress Scale (ADOSS), salivary cortisol, metabolic and clinical parameters and Letter Cancellation Test (LCT) score were measured at baseline and post-intervention (5–6 months). Results: The yoga group showed statistically significant differences in the mean ADOSS score, metabolic parameters, salivary cortisol, and LCT scores compared to the education group. In the intention- to- treat analysis, a significant reduction [5.11, 95% CI (4.78, 5.36), p = 0.001] in ADOSS score was seen in the yoga group compared to education. Conclusion: Implementation of a 17-week standardized yoga program at the school level significantly decreased stress, improved attention and concentration, metabolic and clinical parameters in Indian adolescents. Trial registration: This trial was registered at Clinical Trials Registry, India (CTRI/2017/08/009203).